2020
DOI: 10.23937/2474-3658/1510140
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Using Insecticides Treated Nets (ITNs) in Curbing Malaria in Nigeria: A 2000-2018 Systematic Review

Abstract: The proper use of Insecticides treated nets (ITNs) has been adjudged an efficacious and cost-effective method for curbing malaria. Despite the distribution of ITNs in Nigeria, malaria remains one of the major causes of morbidity and mortality, especially among children below 5-years-old. This systematic review was intended to document the factors mitigating the use of ITNs in Nigeria. Scholarly articles published from the year 2000 through 2018 were reviewed. Six (6) databases (Medline, PubMed, Cinahl Plus, Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Their effectiveness is two times that of untreated nets and their protective role when used is highly rated when compared with no nets 4 . Results from previous studies showed that the use of ITNs led to the reduction of new cases of uncomplicated malaria by half and to a>16% reduction in mortality compared to settings that did not use nets 3,5 . This explains why the Federal Government of Nigeria and non-governmental organizations (NGOs) embarked on the provision and distribution of ITNs to vulnerable groups and to the entire population at large 5 .…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Their effectiveness is two times that of untreated nets and their protective role when used is highly rated when compared with no nets 4 . Results from previous studies showed that the use of ITNs led to the reduction of new cases of uncomplicated malaria by half and to a>16% reduction in mortality compared to settings that did not use nets 3,5 . This explains why the Federal Government of Nigeria and non-governmental organizations (NGOs) embarked on the provision and distribution of ITNs to vulnerable groups and to the entire population at large 5 .…”
Section: Introductionmentioning
confidence: 98%
“…Malaria is endemic in the poorest countries of the world, causing hundreds of millions of clinical cases and more than 2.6 million deaths each year 2 . More than 90% of malaria deaths occur in Sub-Saharan Africa, resulting in an estimated 3000 deaths per day 3 . Mortality due to malaria occurs in…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations